Digital Framework for Bridge Parametric Design: The BIM Library approach - Surovtsev, Iurii (Auckland University of Technology, 2024)
This article explores the impact of Building Information Modelling (BIM) in bridge construction. It emphasises BIM’s capacity to enhance design, construction, and management efficiency in infrastructure projects, notably bridges. Despite the evident advantages of BIM, the construction industry exhibits a general reluctance towards its widespread adoption. A significant gap is identified in developing data schemas for civil infrastructure, including bridges, which necessitates a more detailed data schema and a dedicated framework for bridge engineering. The article reviews the benefits and barriers to BIM implementation, highlighting the role of government regulations as a potential catalyst for adoption. It also discusses the concept of a National BIM Object Library as a solution to promote collaboration and efficiency in building projects. The paper proposes an approach for establishing a BIM object library for bridge design, focusing on geometrical data and element decomposition. This includes an examination of existing practices, as well as NBS requirements, to develop guidelines for BIM object templates. The proposed framework aims to standardise geometrical and semantic data sets for Bridge design, fostering a more sustainable, efficient, and innovative future in civil engineering.